Benchmarking: Primerjalna analiza v turizmu - Mlakar , Nadja; Pavlakovič Farrell, Barbara (University of Maribor Press, 2025)
Benchmarking: Comparative Analysis in Tourism. The textbook "Benchmarking – Comparative Analysis in Tourism" offers a detailed insight into the benchmarking process which is used to evaluate and improve businesses, organizations, and tourist destinations. The authors first present the theoretical foundations of benchmarking, including definitions, types, and phases of the analysis. The second part of the textbook focuses on practical examples carried out by students at the Faculty of Tourism at the University of Maribor. This allows readers to understand how theoretical concepts are applied in the real world in real case studies. It includes specific examples of benchmarking analysis that address various tourist destinations, providing valuable insights into successful practices and strategies. The textbook is designed to serve as a learning tool for students and professionals in tourism while also promoting the use of benchmarking as a tool for enhancing tourism offerings and sustainable development. Thus, the textbook contributes to the understanding and implementation of benchmarking in the tourism industry.